Short-term Results of Laparoscopic Totally Extraperitoneal Inguinal Herniorrhaphy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: The local experience of laparoscopic totally extraperitoneal (TEP) hernia repair in Chittagong were reviewed.Methods: Between January 2009 to December 2010, 30 consecutive patients underwent TEP hernia repairs for inguinal hernia. A retrospective case series of 30 consecutive patients undergoing TEP 1 year ago by a single surgeon was followed prospectively with a focused physical examination and interview. Data collected included recurrence, chronic groin pain, tenderness, sensory disturbance, activity or occupational limitation and personal satisfaction.Results: The mean age was 56 years. Median follow-up was 1 month. Follow-up was completed by interview and physical examination. There was no major morbidity or mortality. Hernia recurrence rate was 3.33%. Chronic pain occurred in 2 patients (6.66%), which was mild in nature. Ninety-seven per cent of patients were satisfied with their repair and would or had recommended TEP to others.Conclusions: Short-term results of TEP demonstrated be an effective and safe procedure with a low recurrence and low prevalence of chronic pain that is generally of a mild, infrequent nature.DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.24Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 30-33